Maternal age, parity, and gestational age of pregnancy of hypertensive pregnancy disorders - Elizawarda; Khodijah, Dodoh; Sinaga, Maya Handayani (BKM Public Health and Community Medicine, 2022)
Purpose: This study aims to determine the factors of maternal age, parity, and gestational age contributing to hypertensive pregnancy disorders in Deli Serdang District Hospital. Methods: This type of research is observational analytic with a cross-sectional approach to look at maternal age, parity, and gestational age factors for the occurrence of hypertensive pregnancy disorders in Deli Serdang District Hospital in 2018. The sample was 72 people. Data were analyzed by frequency distribution and Chi-Square test with p≤0.05. Results: Most cases of hypertensive disorders in pregnancy fall within the severe preeclampsia category, with the majority occurring among mothers aged 20-35 years and with a parity range of 2-42. Over three-quarters of these cases manifest during the third trimester. There is a significant correlation between maternal age, parity, and the incidence of preeclampsia. Conclusion: Maternal age and parity have a significant relationship with hypertensive pregnancy disorders. Health workers should always screen for severe preeclampsia even though pregnant women are not at risk.